Eutrophication of Dandaru reservoir in Ibadan, Nigeria in relation to land-use and mechanical desilting (2016)
Eutrophication of water bodies is mainly caused by influx of Nitrogen and phosphorus compounds from land-use. Understanding relationship water reservoirs and farmlands will foster management of ecological resources. This study examined the link between eutrophication and land-use at Dandaru reservoir at Agodi, Ibadan, Oyo State and effect (s) of mechanical clean up on the reservoir. The Vegetation, soil of Lawn (L), bush fallow (BF), vegetable farm (VF) and Agodi Gardens (AG), and water quality of Dandaru reservoir in Ibadan were systematically assessed pre- and post-desilting following standard procedures. Forty 0.25 m2 quadrats were floristically assessed for Relative importance values (RIV) and Shannon-Weiner index (H`). Three randomly extracted bulked and sub-sampled top soil of each land-use were analysed physiochemically. The reservoir was sampled for phosphate, Organic carbon (TON), nitrate (TN), dissolved oxygen (DO) and pH in three replicates at entry, mid and exit points of the river. Data were analysed using ANOVA at p=0.05. Means statistical differences followed Fisher’s LSD. Fifty one plant species were enumerated pre-desilting consisting of 15, 22, 29 and 11 species in L, BF, VF and AG respectively; 22 plants were enumerated post-silting consisting 10, 10, 8 and 8 species in L, BF, VF and AG respectively. legumes ranged in RIVs from 4.217-8.397 in BF and VF. Pre-desilting, VF had highest H` (3.334), while AG had lowest (1.988). Post-desilting, Lawn had highest H` (1.956) while VF had lowest (1.679). P, TOC, TN and pH were significantly different in all land-uses with TN (0.81±0.02g/kg) and TOC (7.83±0.05g/kg) in BF. Phosphorus (0.31±0.03g/kg) was high at AG pre-desilting. Post-desilting, TN (32.90±3.37g/kg) and TOC (2.24±0.04g/kg) were significantly high in lawn. Pre-silting, pH and DO were significantly different at all points, lowest at midpoint (6.73±0.04mg/l and 7.89±0.30mg/l respectively); post-silting, pH (7.87±0.00) and DO (9.54±0.0Img/l) increased at midpoint.The legumes in agricultural lands most likely contributed to eutrophication of Dandaru reservoir. However, desilting offered temporary restoration. Cessation of agricultural activities around Dandaru reservoir with its periodic assessment will prevent eutrophication